RELIGION AND ACTUALIZATION OF SPIRITUAL ESSENCE - Конотоп, Л. Г. (Proceedings of the National Aviation University Series Philosophy Cultural, 2016)
This paper analyzes the socio – political and ideological changes in society that directly affect the spiritual potential of man. Religion is seen as a significant element of society, which activates the creative potential of people, their desire for spiritual and emotional fulfillment.